FACTORS AFFECTING ECONOMIC GROWTH OF THE AGRICULTURAL SECTOR IN KARANGANYAR REGENCY - Suryanto, Fajar; Kusnandar; Antriyandarti, Ernoiz (PT. Media Edutama Nusantara, 2024)
ABSTRACT Different regions across Indonesia play crucial roles in advancing the national economy. The regional governments, with their in-depth understanding of local conditions, are best positioned to create policies that align with community needs and foster regional economic development. This research aims to analyze the impact of working capital distribution, investment credit, labor force size, and agricultural land area on economic growth within the agricultural sector in Karanganyar Regency. This study employs an empirical method combined with quantitative research techniques. To meet the data requirements, the researcher used secondary data from Karanganyar Regency for the years 2011–2021. Multiple linear regression analysis techniques were utilized for data analysis. The findings indicate that the distribution of working capital credit and the amount of arable land significantly impact the economic growth of Karanganyar Regency's agricultural sector. In contrast, the distribution of investment credit and the number of productive workers do not have a significant impact. Keywords: Working Capital Credit, Investment Credit, Number of Labor Force, Agricultural Land Area, Economic Growth in the Agricultural Sector